The impact of COVID-19 on delayed presentations of necrotising fasciitis. Issue 2 (6th February 2022) - Nguyen, Quoc Dung; Diab, Jason; Khaicy, David; Diab, Vanessa; Hopkins, Zachias; Foong, Lai Heng; Berney, Christophe R
Abstract: The purpose of this study was to determine the impact of coronavirus disease 2019 (COVID-19) on the delayed presentation of necrotising fasciitis (NF). A retrospective study was conducted of adult patients (≥16 years old) diagnosed with NF at a hospital from 2017 to 2020. A quantitative comparative analysis for the COVID-19 group and control group between 2017 and 2019. Structured interviews were conducted to examine the impact of COVID-19 on patients. There were 6 patients in the COVID-19 group and 10 patients in the control group. The COVID-19 group had a longer mean onset of symptoms till hospital presentation of 4.1 days and a longer mean operative time. The COVID-19 group was more likely to be admitted to intensive care unit. Three patients in the COVID-19 group did not survive compared to survival in the counterparts. Participant responses indicated the COVID-19 pandemic did not prevent them from presenting to ED.